2022
DOI: 10.1029/2022gl098511
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow of the Night: First Direct Observation of a SAR Arc Evolving Into STEVE

Abstract: During the 17 March 2015 geomagnetic storm, citizen scientist observations from Dunedin (45.95°S, 170.32°E), New Zealand, revealed a bright wide red arc known as stable auroral red (SAR) arc evolving into a thin white‐mauve arc, known as Strong Thermal Emission Velocity Enhancement (STEVE). An all‐sky imager at the Mount John Observatory (43.99°S, 170.46°E), 200 km north of Dunedin, detected an extremely bright arc in 630.0 nm, with a peak of ∼6 kR, colocated with the arc measured at Dunedin at an assumed heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 34 publications
9
33
0
Order By: Relevance
“…The electron flux above a few tens of keV for the 2:46 UT event was substantially higher than that for the other injections (Figure 3K). This event supports the finding by Nishimura et al, (2020b) that the strong electron injection to the dusk side magnetosphere could be the driver for intense subauroral 3 Fine-scale structures of STEVE STEVE, in some images, appears as a homogeneous arc with little structure along the arc [e.g., Archer et al, 2019b;Martinis et al, 2022;Parnikov et al, 2022]. Wilson (1891) and Stormer (1935) perceived STEVE-like emissions as a luminous band such as a comet tail and homogeneous arc.…”
Section: Occurrence Characteristicssupporting
confidence: 82%
See 2 more Smart Citations
“…The electron flux above a few tens of keV for the 2:46 UT event was substantially higher than that for the other injections (Figure 3K). This event supports the finding by Nishimura et al, (2020b) that the strong electron injection to the dusk side magnetosphere could be the driver for intense subauroral 3 Fine-scale structures of STEVE STEVE, in some images, appears as a homogeneous arc with little structure along the arc [e.g., Archer et al, 2019b;Martinis et al, 2022;Parnikov et al, 2022]. Wilson (1891) and Stormer (1935) perceived STEVE-like emissions as a luminous band such as a comet tail and homogeneous arc.…”
Section: Occurrence Characteristicssupporting
confidence: 82%
“…The fine-scale structures of STEVE drift westward along the arc, and the speed seems to correspond to the intense SAID flow speed (Gillies et al, 2020). The exposure time may affect the detectability of fine-scale structures in photographs, but the photographs by Martinis et al (2022) and Figures 1 and 4, have similar exposure times (10, 13, and 10 s). There may also be conditions in the magnetosphere−ionosphere system that create fine-scale structures of STEVE.…”
Section: Occurrence Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, the interest in SAID has been refreshed by the recognition and observations of the Strong Thermal Emission Velocity Enhancement (STEVE) optical phenomena. While the STEVE generation mechanism remains unclear to date, it is now well established that STEVE is collocated with intense SAID channels (Archer et al., 2019; Chu et al., 2019; MacDonald et al., 2018; Martinis et al., 2022; Nishimura et al., 2019; Nishimura, Donovan, et al., 2020). The STEVE‐related SAID channels have larger flow speeds (in excess of 4 km/s), hotter electrons with temperatures up to ∼10 4 K, and density troughs deeper than 10 4 cm −3 in the F region.…”
Section: Introductionmentioning
confidence: 99%
“…MacDonald et al (2018) reported for the first time on the connection of this phenomenon with SAID. Follow-on studies, several of them utilizing citizen science images, reveal a multitude of previously unknown aurora-untypical characteristics (spectral composition, height, not-field aligned structures, location), see reference list: Archer et al (2019aArcher et al ( , 2019b, Chu et al (2020), Harding et al (2020), Gallardo-Lacourt et al (2018a, 2018b, Gillies et al (2019Gillies et al ( , 2020, Liang et al (2019), Martinis et al ( 2021Martinis et al ( , 2022, Mende & Turner (2019), Mende et al (2019), Nishimura et al (2019Nishimura et al ( , 2020, and Semeter et al (2020).…”
Section: Steve (Strong Thermal Emission Velocity Enhancement) Is a Su...mentioning
confidence: 99%